Perbedaan Fi’il Lazim dan Fi’il Muta’addi dalam Naskah Al-Qawa’id Al-Asasiyyah: Kajian Kaidah Bahasa Arab - Fanisa Putri Anggraini; Siti Nurbaya; Arif Rizky; Hudaidah Hudaidah; Risa Marta Yati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the concepts of fi’il lazim and fi’il muta’addi found in the manuscript Al-Qawa’id al-Asasiyyah and to examine the differences between the two in Arabic sentence structure. This study is motivated by the importance of understanding the verb system in Arabic, particularly in determining the relationship between verbs, subjects (fa’il), and objects (maf’ul bih) in sentence formation. This research employed a qualitative method using a text analysis approach. The primary data source was obtained from the book Al-Qawa’id al-Asasiyyah, while secondary data were collected from various books and scientific journal articles related to nahwu studies. Data collection was conducted through a literature study by recording parts of the text discussing fi’il lazim and fi’il muta’addi. The data analysis process involved several stages: translating the manuscript, identifying the types of verbs in the text, classifying the data based on their characteristics, comparing the two types of verbs, and drawing conclusions from the analysis. The results show that fi’il lazim are verbs that do not require an object because their meaning is complete with only the verb and the subject, whereas fi’il muta’addi are verbs that require an object to complete the meaning of the action in the sentence. The difference between the two mainly lies in the relationship between the verb and the object in sentence structure. These findings indicate that understanding the concepts of fi’il lazim and fi’il muta’addi is essential for analyzing Arabic sentence structure and understanding the use of verbs in the text Al-Qawa’id al-Asasiyyah